Uji Alat Kekeruhan Air Menggunakan Turbidity Sensor Berbasis Arduino - Refpo Rahman (Program Studi Pendidikan Fisika, UIN Raden Fatah Palembang, 2021)
The water turbidity tester has designed using a turbidity sensor based on Arduino Uno to measure water turbidity levels. Testing the instrument is divided into two stages. The first stage, calibration testing using five samples symbolized by sample A-E. This sample is measured to obtain the voltage output from the water turbidity tester and the water turbidity level (NTU) from the standard tool. The results have obtained sample A (4.17 V and 3.014 NTU), sample B (4.066 V and 43.02 NTU), sample C (3.864 V and 225 NTU), sample D (3.798 V and 312 NTU), and sample E (2.49 V and 3000 NTU). This measurement value is used to calibrate the water turbidity level. In the second stage, the calibrated tools are re-tested with NTU output data. This measurement is used to calculate the relative error by comparing the data. The result shows that the smallest error rate when measuring the sample is> 220 NTU with an error rate below 10%. Meanwhile, the largest error rate when measuring water turbidity is <220 NTU with an error rate of above 10% to 100%. Keyword: Arduino Uno; Turbidity Sensor; water turbidity tool.